2022
DOI: 10.1101/2022.08.22.504730
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metabolic enhancement of mammalian developmental pausing

Abstract: The quest to model and modulate embryonic development became a recent cornerstone of stem cell and developmental biology. Mammalian developmental timing is adjustable in vivo by preserving preimplantation embryos in a dormant state called diapause. Inhibition of the growth regulator mTOR (mTORi) pauses mouse development in vitro, yet constraints to pause duration are unrecognized. By comparing the response of embryonic and extraembryonic stem cells to mTORi-induced pausing, we identified lipid usage as a bottl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 74 publications
2
2
0
Order By: Relevance
“…As LIF signalling is associated with diapause where differentiation is indefinitely stalled 80 , the support of this signalling pathway within the DP population could reflect a general role in blocking commitment and expansion of a plastic cell type. The dependence on oxidative phosphorylation in DP nEnd is also consistent with the capacity of increased fatty acid oxidation to support embryo longevity and enhanced diapause via suppression of glycolysis 81 . As we observe here that the DP population proliferates faster than Pdgfra + nEnd, this might explain our earlier observations that LIF signalling supports expansion of the PrE compartment in vivo 47 .…”
Section: Discussionsupporting
confidence: 66%
“…As LIF signalling is associated with diapause where differentiation is indefinitely stalled 80 , the support of this signalling pathway within the DP population could reflect a general role in blocking commitment and expansion of a plastic cell type. The dependence on oxidative phosphorylation in DP nEnd is also consistent with the capacity of increased fatty acid oxidation to support embryo longevity and enhanced diapause via suppression of glycolysis 81 . As we observe here that the DP population proliferates faster than Pdgfra + nEnd, this might explain our earlier observations that LIF signalling supports expansion of the PrE compartment in vivo 47 .…”
Section: Discussionsupporting
confidence: 66%
“…Proteomic analysis pointed to fatty acids as a mouse-specific energy source utilized to sustain pausing (Figure 5e, S7a). We and others have recently shown that, indeed, fatty acids derived from lipid droplets are actively used during mouse diapause (20,43), and that enhancing fatty acid oxidation by L-carnitine supplementation significantly prolongs in vitro pausing duration of mouse blastocysts (20). Consistent with species-specific energy sources, L-carnitine supplementation of human blastoids during pausing did not alter the culture duration (Figure S7b).…”
Section: Species-specific Tempo and Metabolism Of Developmental Pausingsupporting
confidence: 65%
“…This paused pluripotent state is reversible and pause-released embryos and ESCs can give rise to live, fertile mice and high-grade chimeras, respectively (1). Downstream of mTORi, paused cells display reduced global transcription and translation, and altered metabolic networks (20). The transcriptional profile of mTORi-paused ESCs closely resembles that of the in vivo diapaused epiblast, suggesting that mTOR may be the master regulator of developmental pausing also in vivo.…”
Section: Introductionmentioning
confidence: 93%
“…This is consistent with dependence of DP nEnd on oxidative phosphorylation, which, in turn, is linked to enhanced diapause via suppression of glycolysis. 109 …”
Section: Discussionmentioning
confidence: 99%